ERSN-OpenMC-Py: A python-based open-source software for OpenMC Monte Carlo code - Lahdour, M.; El Bardouni, T.; El Hajjaji, O.; EL Bakkali, J.; Al-Zain, J.; Oulad-Belayachi, S.; Ziani, H.; Idrissi, Abdelghani; El Maliki El Hlaibi, S. (Computer physics communications, 2024)
The graphical user interface is a key element in facilitating the use of complex simulation software. This project describes the development of a graphical user interface called “ERSN-OpenMC-Py” for an existing neutron simulation code, OpenMC. The main goal is to make simulation more accessible to a wider audience by providing a user-friendly and intuitive user interface. The process of developing the graphical user interface is described in detail, including the different stages of development such as user interface design, user interface implementation, and user interface integration with the OpenMC simulation code. The development tools used, such as Python3 and PyQt5, are also explained. The user interface allows the user to control the simulation parameters and interact with the simulation results. Key features of the user interface include visualization of simulation results, modification of simulation parameters, saving and loading simulation configurations, as well as managing output files. The end result is a functional user interface that allows users to easily visualize simulation results and control simulation parameters in an intuitive manner. This user interface also provides a better user experience for non-programming experts who wish to use the simulation code for their own projects. Program Title: ERSN-OpenMC-Py, version 1.0 CPC Library link to program files:https://doi.org/10.17632/83xrdht7mz.1 Developer's repository link:https://github.com/mohamedlahdour/ERSN-OpenMC-Py Licensing provisions: GPLv2 Programming language: Python 3 External routines/libraries: NumPy, Matplotlib, PyQt5 Nature of problem: The program is designed to be utilized in the everyday workflow for tasks such as preparing input files for the OpenMC code and analyzing the resulting calculations. Solution method: The graphical user interface of the OpenMC is created using PyQt5. Figures are plotted by means of matplotlib library.